Linking Knowledge: A Qualitative Analysis of Gender and IWRM-related Policies in the Upper East Region of Ghana - Lasiter, Kalie; Stawicki, Stephanie (2014)
While this study was originally conducted to gather baseline data on the general activities, issues, and concerns of women in the Upper East Region in northern Ghana, the initial data collection led to the discovery that women in the Upper East Region are organized, either by their own accord or through the recommendation of local governing bodies, in social groupings that fulfill specific needs such as access to credit, access to agricultural inputs, and access to reciprocal labor and support. The objective of the study shifted to include an analysis of the processes, opportunities and constraints of how and why women organize themselves in these particular social groupings. The paper concludes with an evaluation of how, if at all, IWRM-related district, regional and national level policies from government departments such as the Ministry of Food and Agriculture (MOFA), the Ministry of Women’s and Children’s Affairs (MOWAC), and the Ministry of Water Resources, Works and Housing (MWRWH) address women and their social networks in Ghana.